KLF4 Inhibits the Differentiation of Goat Intramuscular Preadipocytes Through Targeting C/EBPβ Directly - Xu, Qing; Li, Yanyan; Lin, Sen; Wang, Yong; Zhu, Jiangjiang; Lin, Yaqiu (Frontiers in Genetics, 2021)
Intramuscular fat (IMF) deposition is a complicated process, and most of the underlying regulators of this biological process are unknown. Here, we cloned the intact CDS of KLF4 gene and investigated the role of KLF4 by gaining or losing function in vitro, and further explored the pathways of KLF4 regulating differentiation of intramuscular preadipocytes in goat. Our results show that goat KLF4 gene consists of 1536 bp encoding a protein of 486 amino acids. The expression of KLF4 is higher in lung, while lower in heart and muscle in goat. Knockdown of KLF4 mediated by siRNA technique significantly promotes intramuscular preadipocytes lipid accumulation and up-regulates mRNA expression of adipogenic related genes including C/EBPα, C/EBPβ and PPARγ in vivo cultured cells. Consistently, overexpression of KLF4 inhibits intramuscular adipocytes lipid accumulation and significantly down-regulation gene expression of C/EBPβ, PPARγ, aP2 and Pref-1. Further, we found that other members of KLFs were up or down regulated after interference or overexpression of KLF4, including KLF 2, 5-7. We also found that C/EBPβ was a potential target of KLF4, because it had an opposite expression pattern with KLF4 during the differentiation of intramuscular preadipocytes and had putative binding sites of KLF4. The dual-luciferase reporter assay indicated that overexpression of KLF4 inhibited the transcriptional activity of C/EBPβ. These results demonstrate that KLF4 inhibits the differentiation of intramuscular preadipocytes in goat by targeting C/EBPβ.